2019
DOI: 10.3390/biom10010059
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Quercetin in Alzheimer’s Disease

Abstract: Quercetin is a flavonoid with notable pharmacological effects and promising therapeutic potential. It is widely distributed among plants and found commonly in daily diets predominantly in fruits and vegetables. Neuroprotection by quercetin has been reported in several in vitro studies. It has been shown to protect neurons from oxidative damage while reducing lipid peroxidation. In addition to its antioxidant properties, it inhibits the fibril formation of amyloid-β proteins, counteracting cell lyses and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
226
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(230 citation statements)
references
References 146 publications
(138 reference statements)
1
226
0
3
Order By: Relevance
“…This study confirms the ability of quercetin loaded niosomes to reverse CCl 4 intoxication and to carry out an antioxidant effect.Pharmaceutics 2020, 12, 143 2 of 18 and anticancer activities [1][2][3]. These intrinsic properties, together with their biocompatibility and remarkable antioxidant activity, have attracted researchers' attention to explore potential therapeutic applications [4,5].Quercetin (3, 30, 4, 5, 7-pentahydroxyflavone) is probably the most studied bioflavonoid, belonging to the family of flavonols; its therapeutic applications include hepatoprotection [6], prevention of neural cell apoptosis [7] and cancer chemo-prevention and treatment [8].Quercetin acts as strong antioxidant by scavenging free radicals and transition metal ions, thus decreasing the process of lipid peroxidation, which is responsible for the development of many diseases, e.g., cardiovascular and neurodegenerative diseases, as well as liver damage [9][10][11].However, quercetin therapeutic applications present challenges due to (i) low aqueous solubility, (ii) photo and oxidative degradability, (iii) high first-pass effect, (iv) poor intestinal absorption and, hence, low systemic bioavailability [12][13][14][15].In order to overcome these problems, which are common among flavonoids, drug delivery systems (DDS) including emulsions, cyclodextrins, polymeric nanoparticles, micelles and liposomes have been used to enhance their pharmaceutical properties [16][17][18].Out of various DDS, niosomes are similar to liposomes in structures, preparation techniques, and physical properties. Niosomes possessed many advantages, including (i) biocompatibility, (ii) improved stability, (iii) non-immunogenicity, (iv) sustained drug release and (v) low preparation cost [19][20][21][22].Non-ionic surfactants, which present high safety and biocompatibility, have been selected over ionic surfactants for the preparation of these vesicles because anionic and cationic charges presented irritant and cytotoxic effects, respectively [23,24].Non-ionic surfactants are comprised of both polar and nonpolar segments and possess high interfacial activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirms the ability of quercetin loaded niosomes to reverse CCl 4 intoxication and to carry out an antioxidant effect.Pharmaceutics 2020, 12, 143 2 of 18 and anticancer activities [1][2][3]. These intrinsic properties, together with their biocompatibility and remarkable antioxidant activity, have attracted researchers' attention to explore potential therapeutic applications [4,5].Quercetin (3, 30, 4, 5, 7-pentahydroxyflavone) is probably the most studied bioflavonoid, belonging to the family of flavonols; its therapeutic applications include hepatoprotection [6], prevention of neural cell apoptosis [7] and cancer chemo-prevention and treatment [8].Quercetin acts as strong antioxidant by scavenging free radicals and transition metal ions, thus decreasing the process of lipid peroxidation, which is responsible for the development of many diseases, e.g., cardiovascular and neurodegenerative diseases, as well as liver damage [9][10][11].However, quercetin therapeutic applications present challenges due to (i) low aqueous solubility, (ii) photo and oxidative degradability, (iii) high first-pass effect, (iv) poor intestinal absorption and, hence, low systemic bioavailability [12][13][14][15].In order to overcome these problems, which are common among flavonoids, drug delivery systems (DDS) including emulsions, cyclodextrins, polymeric nanoparticles, micelles and liposomes have been used to enhance their pharmaceutical properties [16][17][18].Out of various DDS, niosomes are similar to liposomes in structures, preparation techniques, and physical properties. Niosomes possessed many advantages, including (i) biocompatibility, (ii) improved stability, (iii) non-immunogenicity, (iv) sustained drug release and (v) low preparation cost [19][20][21][22].Non-ionic surfactants, which present high safety and biocompatibility, have been selected over ionic surfactants for the preparation of these vesicles because anionic and cationic charges presented irritant and cytotoxic effects, respectively [23,24].Non-ionic surfactants are comprised of both polar and nonpolar segments and possess high interfacial activity.…”
mentioning
confidence: 99%
“…Quercetin acts as strong antioxidant by scavenging free radicals and transition metal ions, thus decreasing the process of lipid peroxidation, which is responsible for the development of many diseases, e.g., cardiovascular and neurodegenerative diseases, as well as liver damage [9][10][11].…”
mentioning
confidence: 99%
“…It has been demonstrated that quercetin possesses a neuron-protective effect by alleviating oxidative stress and inflammation. Khan et al further refine the effect and underlying mechanisms of quercetin on AD, with an emphasis on cognitive performance [ 14 ]. Finally, quercetin is proposed to offer potential as a lead compound for clinical application in such disease.…”
Section: Treatment Of Diseasesmentioning
confidence: 99%
“…Quercetin, 3,3′,4′,5,7-pentahydroxyflavanone, is one of the most powerful antioxidants of various edible plants. It exerts various therapeutic effects including anti-inflammatory, anticancer, anti-allergic, anti-infective, and neuroprotective efficacies [ 69 ]. Quercetin attenuated mitochondrial dysfunctions by inhibiting ROS production and increased the activity of SOD and ATP generation by activating the AMP-activated protein kinase (AMPK) pathway, thereby reducing Aβ-induced neurotoxicity [ 70 ].…”
Section: Neuroprotective Effects Of Potential Natural Compounds Anmentioning
confidence: 99%